(untitled) (Sciences & Technologie. C, Biotechnologies, 2006)
The present investigation was carried out under the green house conditions to study the salt stress effect on growth, some organic materials and productivity of durum wheat (Triticum durum Var hedba 3), and to alleviate by applying the phytohormones as seed soaking (IAA-7ppm, GA3-250ppm, kinetin-100ppm) and foliar spray (IAA-0.5ppm, GA3-50ppm, kinetin-20ppm). The salt stress decreased significantly the growth and productivity of durum wheat and induced significant decrease in the leave chlorophyll content, proteins, while proline showed a significant increase. Applying of phytohormones on the salt stressed plant (150 mM NaCl), especially as seed soaking, showed a different effect compared to salt stress effects through stimulating the growth and productivity. Moreover phytohormones applications induced significant increase in the content of chlorophyll, proteins, amino acids and proline.